2005
DOI: 10.1210/jc.2005-1389
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant, Nonglycosylated Human Insulin-Like Growth Factor-Binding Protein-3 (IGFBP-3) Is Degraded Preferentially after Administration to Type II Diabetics, Resulting in Increased Endogenous Glycosylated IGFBP-3

Abstract: After administration to diabetics, nonglycosylated IGFBP-3 is degraded more rapidly than glycosylated IGFBP-3. By acting as a preferential substrate for the IGFBP-3 protease, nonglycosylated IGFBP-3 protects endogenous, glycosylated IGFBP-3 from degradation, allowing total IGFBP-3 concentrations to increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Work reported by Clemmons et al (40) demonstrates an induction of IGFBP-3 proteolysis, which is preferential for the nonglycosylated form, after the administration of IGF-I/IGFBP-3 complex to subjects with type 2 diabetes. The mechanism and relevance of this induction in proteolysis has not yet been clarified.…”
Section: Discussionmentioning
confidence: 93%
“…Work reported by Clemmons et al (40) demonstrates an induction of IGFBP-3 proteolysis, which is preferential for the nonglycosylated form, after the administration of IGF-I/IGFBP-3 complex to subjects with type 2 diabetes. The mechanism and relevance of this induction in proteolysis has not yet been clarified.…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that the decrease in ALS limits the degree of increase in IGFBP-3. The degree of increase could also be limited by IGFBP-3 proteolysis, which is known to be increased in diabetic plasma (29). The net result of these changes would be that free IGF-I levels would increase relative to the increase in total IGF-I, thus limiting the ability of IGFBP-3 to control the rate of efflux of IGF-I from the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…According to Cortizo et al, levels of IGF-I and IGFBP-3 were comparable in the type 2 diabetic patients and controls for the population ranging from 35 to 70 years [9]. The amount of intact IGFBP-3 depends on the rate of its synthesis, a degree of proteolysis, which increases in diabetes [14,25], and the severeness of diabetic nephropathy, which slowers the clearance rate of IGFBP-3 [26]. Clemmons et al [14] have demonstrated that the non-glycosylated IGFBP-3 is degraded more rapidly than the glycosylated IGFBP-3.…”
Section: Discussionmentioning
confidence: 97%
“…The amount of intact IGFBP-3 depends on the rate of its synthesis, a degree of proteolysis, which increases in diabetes [14,25], and the severeness of diabetic nephropathy, which slowers the clearance rate of IGFBP-3 [26]. Clemmons et al [14] have demonstrated that the non-glycosylated IGFBP-3 is degraded more rapidly than the glycosylated IGFBP-3. If methodological differences in IGFBP-3 assays are taken into account (some immunoassays measure only intact IGFBP-3, whereas others measure both intact and fragmented molecules) [27], the search for more accurate data on IGFBP-3 levels in diabetics is still actual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation